PENGARUH KOMPENSASI FINANSIAL TERHADAP PRODUKTIVITAS KARYAWAN PT. TELKOM WILAYAH TELEKOMUNIKASI RIAU DARATAN - Yuriza, Xhintica Wulanda Yuriza Wulanda; Indrawat, Henny Indrawat; Trisnawati, Fenny Trisnawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak: This study aims to determine the effect of financial compensation on the productivity of employees of PT. Telkom Regional Telecommunications Riau. The population in this study were all employees of PT. Telkom Regional Telecommunications Riau numbering 180 employees and determination of the samples using techniques Proportionate Stratified Random Sampling which are planted 64 people. The data used is primary data that questionnaires (questionnaire) filled respondents. While data analysis using validity, reliability test, and hypothesis testing. From the results of this study concluded that: (1) financial compensation given PT. Riau Regional Telecommunications Telkom to employees can be categorized either. Similarly, the productivity of the employees of PT. Telkom Regional Telecommunications Riau mainland is also considered good because the percentage is between 56% -75%; (2) financial compensation have an effect on the productivity of employees of PT. Telkom Regional Telecommunications Riau. If the financial compensation given PT. Riau Regional Telecommunications Telkom increased the produktivits employees is expected to increase. Advice can be given: (1) PT. Riau Regional Telecommunications Telkom should maintain and enhance financial compensation granted to employees. Because the provision of financial compensation to give effect to an increase in employee productivity; (2) PT. Riau Regional Telecommunications Telkom needs to do a further review to keep the level of productivity of employees at a level in line with expectations the company to support the company in achieving its goals. And do not rule out the possibility the company to be able to open up reviewing studies from external parties under review increased productivity of the employees. Keywords: financial compensation, productivity.